Sinonasal Bone Destruction caused by Frontal Meningioma Invasion related with Respiratory Tract Infection Incident: A Case Report - Adji, Novan Krisno; Putri, Komang Yunita Wiryaning; Indreswari, Laksmi; Nugraha, Muhammad Yuda (Jember Medical Journal, 2022)
Meningioma is uncommonly found in extracranial. Extracranial meningioma can be extension from primary intracranial tumors that accompany osteolytic changes in the skull or causes bone destruction. In this article, we report about intracranial meningioma in the frontal region that extend to the sinonasal bone causes bone destruction and being predisposing factor for respiratory tract infection. A 47-years old female brought to the emergency department due to dyspnea and fever since a week ago and there was found a lump in the frontal region. During the surgical procedure, there was invasion of tumor and caused sinonasal bone destruction. The endotracheal tube (ETT) can be seen from the surgical field. In this case the patient was threated pneumonia infection, it can be related as complication of sinonasal bone destruction that caused by invasion of meningioma to extracranial manifestation. The clinical important that must be informed to the patient the possibility of recurrent respiratory tract infection incidents.